2000
DOI: 10.1017/s0790966700005723
|View full text |Cite
|
Sign up to set email alerts
|

A case of co-existent Capgras and deClèrambault's syndrome with a history of morbid jealousy

Abstract: A patient presenting with co-existent Capgras and deClerambault's syndromes, with a history of morbid jealousy is described. This combination of syndromes has not previously been described. The relevant literature to this case is reviewed, in relation to the onset of these syndromes, aetiology and treatment. Abnormalities in pathways involving recognition of familiar faces have been implicated in a number of similar cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Conversely, the secondary form manifests with a gradual onset, an ill-defined disease course, and the potential for substitution of the object of love. This form is associated with various mental disorders such as schizophrenia, bipolar disorder, major depressive disorder, and any subtype of dementia [23,[29][30][31][32][33][34], and may co-occur with Capgras syndrome, Fregoli syndrome, and Folie à Deux syndrome [35][36][37][38]. Notably, erotomania can also be secondary to physical or organic conditions.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Conversely, the secondary form manifests with a gradual onset, an ill-defined disease course, and the potential for substitution of the object of love. This form is associated with various mental disorders such as schizophrenia, bipolar disorder, major depressive disorder, and any subtype of dementia [23,[29][30][31][32][33][34], and may co-occur with Capgras syndrome, Fregoli syndrome, and Folie à Deux syndrome [35][36][37][38]. Notably, erotomania can also be secondary to physical or organic conditions.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Kennedy et al . presented a case report describing the coexistence of de Clerambault's syndrome and Capgras syndrome (a syndrome in which a patient believes that a person, usually close to the subject, has been replaced by an identical double) 35 . Wright et al .…”
Section: Delusional Lovingmentioning
confidence: 99%
“…[28][29][30][31][32][33][34] Kennedy et al presented a case report describing the coexistence of de Clerambault's syndrome and Capgras syndrome (a syndrome in which a patient believes that a person, usually close to the subject, has been replaced by an identical double). 35 Wright et al reported the coexistence of Fregoli syndrome (the affected person believes that another person's mind can inhabit the body of another person) and erotomania. 36 From a forensic perspective, erotomania has been associated with stalking behavior and violent sexual jealousy, and both are more commonly shown by men; 37 it might sometimes involve physical harm or even homicide when the victim spurns the other's affections.…”
Section: Delusional Lovingmentioning
confidence: 99%